The economics of medication safety Improving medication safety through collective, real-time learning - de Bienassis, Katherine (OECD Publishing, 2022)
Poor medication practices and inadequate system infrastructure-resulting in poor adherence, medication-related harms, and medication errors-too often results in patient harm. As many as 1 in 10 hospitalizations in OECD countries may be caused by a medication-related event and as many one in five inpatients experience medication-related harms during hospitalization. Together, costs from avoidable admissions due to medication-related events and added length of stay due to preventable hospital-acquired medication-related harms total over USD 54 billion in OECD countries. This report includes four components; it 1) assess the human impact and economic costs of medication safety events in OECD countries, 2) explores opportunities to improve prescribing practices 3) examines the state-of-the art in systems and policies for improving medication safety, and 4) provides recommendations for improving medication safety at the national level
Keywords: Social Issues/Migration/Health